Recommendations to improve patient‐centred care for ductal carcinoma in situ: Qualitative focus groups with women. (18th September 2019) - Nyhof, Bryanna B.; Wright, Frances C.; Look Hong, Nicole J.; Groot, Gary; Helyer, Lucy; Meiers, Pamela; Quan, May Lynn; Baxter, Nancy N.; Urquhart, Robin; Warburton, Rebecca; Gagliardi, Anna R.
Abstract: Background: Patient‐centred care (PCC) improves health‐care experiences and outcomes. Women with ductal carcinoma in situ (DCIS) and clinicians have reported communication difficulties. Little prior research has studied how to improve communication and PCC for DCIS. Objective: This study explored how to achieve PCC for DCIS. Design: Canadian women treated for DCIS from five provinces participated in semi‐structured focus groups based on a 6‐domain cancer‐specific PCC framework to discuss communication about DCIS. Data were analysed using constant comparative technique. Setting and Participants: Thirty‐five women aged 30 to 86 participated in five focus groups at five hospitals. Results: Women said their clinicians used multiple approaches for fostering a healing relationship; however, most described an absence of desired information or behaviour to exchange information, respond to emotions, manage uncertainty, make decisions and enable self‐management. Most women were confused by terminology, offered little information about the risks of progression/recurrence, uninformed about treatment benefits and risks, frustrated with lack of engagement in decision making, given little information about follow‐up plans or self‐care advice, and received no acknowledgement or offer of emotional support. Discussion and Conclusions: By comparing the accounts of women with DCIS to a PCC framework, we identified limitations and inconsistencies in women's lived experience of communication about DCIS, and approaches by which clinicians can more consistently achieve PCC for DCIS. Future research should develop and evaluate informational tools to support PCC for DCIS.